Etika pengunjung perpustakaan dalam persfektif Alquran - sapril sapril (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
Ethics can be interpreted as reflecting the views of the community for each deed in the form of right and wrong, good and bad at the same time become a benchmark as the difference between the attitude of accepted and rejected in society. It should be understood that ethics is courtesy rules are unwritten, but it must be known. The library visitors must know the principles of ethics in the library, so that maintained comfort and security libraries